Mining (cover)age content analysis on the open-pit mining reportage of community newspapers in Nueva Vizcaya - Lucas, Jamila Van D. (2014)
"This study described how the Vizcaya Advocate and the Valley Journal framed the stories related to the open-pit mining in the province of Nueva Vizcaya. The Agenda-Setting Theory, the Public Sphere Theory, and the Propaganda Model of Media Control were used as lenses for the study. Content analysis was utilized to examine the articles of both community newspapers from January 2011 to September 2013. The researcher found out that most of the articles focused on the less controversial side of mining such as the awards and projects of the mining companies, and the politics involved in it. The stories dealt less about the effects of mining to the environment and the community, and the alleged human rights violations done by the companies. Although stories about the anti-mining movement were published, the sources were poorly quoted and weren't given enough background. Proper context should've been provided for the environmental groups, indigenous people and other sources for the readers to fully understand the anti-mining advocacy. Interviews with the writers and editors of the newspapers revealed that ownership, finances, organizational structure, and other their other affiliations are the factors that affect the framing of the articles. Ethical standards and the function of truth-telling are set aside because of the biases of the writers."